The potential role for acupuncture in treating symptoms in patients with lung cancer: an observational longitudinal study - Kasymjanova, G. (Multimed Inc., 2013)
BACKGROUND: Most lung cancer patients experience multiple symptoms related either to the disease or its treatment. The commonly reported symptoms are pain, depression, anxiety, nausea, and poor well-being. The aim of the present study was to evaluate the effect of acupuncture as a potential treatment modality in symptomatic lung cancer patients. METHODS: This prospective observational study enrolled 33 lung cancer patients from the Peter Brojde Lung Cancer Centre between August 2010 and May 2012. All patients received 45-minute sessions of acupuncture, 1–2 times weekly for a minimum of 4 sessions. Symptom severity was assessed using the Edmonton Symptom Assessment System (esas) before and after completion of acupuncture. RESULTS: The study cohort included 30 patients with non-small- cell lung cancer and 3 with small-cell lung cancer. Mean age was 62 years (range: 36–88 years); 17 of the patients were women. Most of the patients had advanced-stage cancer (73%) and good performance status (Eastern Cooperative Oncology Group 0–1: 88%). Of these patients, 67% received anticancer treatment (chemotherapy or radiotherapy, or both) with acupuncture. Of the remaining 10 patients, 8 received acupuncture after a complete surgical resection of their tumour, and because of their advanced age, 2 received acupuncture and best supportive care. The median number of acupuncture sessions was 7 (interquartile range: 4–13 sessions). Statistically significant improvements in pain, appetite, nausea, nervousness, and well-being were observed. A clinically important improvement (2 points on the esas) was reported by 61% of patients for pain and by 33% for well-being. A significant positive correlation between improved well-being and the number of acupuncture sessions was observed. This correlation remained significant even after controlling for treatment and narcotic use. Receiver operating characteristic analysis demonstrated that a minimum of 6 acupuncture sessions are required for a 70% chance of a clinically important improvement in well-being. CONCLUSIONS: The present study is the first to demonstrate that acupuncture may be an effective approach for improving symptoms—in particular, pain and well–being—in lung cancer patients. Acupuncture is a safe and minimally invasive procedure, and it is potentially useful even in patients undergoing anticancer treatment.